The varied presentation of dermatofibrosarcoma protuberans: a case series of 9 patients treated in single institute - Shiau Ping, Lim; Barathilingam, Kamalbarathi A. L. N. (International Journal of Research in Dermatology, 2021)
Dermatofibrosarcoma protuberans (DFSP) is a rare skin tumor with an estimated incidence of 0.8 to five cases per 1 million people per year. To our surprise, we’d encountered total 9 cases of DFSP with different presentation in our hospital from November 2009-July 2019. One patient with underlying DFSP presented with intraperitoneal bleeding tumor while another 8 patients were newly diagnosed. The mean patient age at the time of diagnosis were 38.4 years. Sex distribution were male in predominance. The anatomical location of tumor varied. Majority presented clinically with slow growing mass on skin/subcutaneous tissue, one tumor grew on a preceding scar, and 2 patients came with bleeding tumors. The median follow-up duration in this series was 23.6 months. Wide local excision was performed in 6 patients, with half of them reported to have surgical margins involved. Reconstruction of the surgical defect took place primarily in 4 patients and split skin graft in 2 patients. Adjuvant radiotherapy was offered to 3 patients with surgical margin involved and disease recurrence. Imatinib was given to one patient with metastatic DFSP prior definitive surgery which was successful. There were no local recurrence or death due to the DFSP course at the end of the follow-up. Final outcome was favorable. Hereby we present the 9 interesting case series.